1997
DOI: 10.1002/(sici)1097-0215(19970611)71:6<1086::aid-ijc27>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of ICAM-1 and its induction by tumor necrosis factor on breast-cancer cellsin vitro

Abstract: In order to study adhesion-molecule expression and its consequences for cellular recognition, the presence of adhesion molecules ICAM-1, VCAM-1, VLA-4, LFA-1, alpha, LFA-1 beta, LFA-3, b1-integrin and b3-integrin was studied on specimens from breast tissue by immunohistochemistry and on cells from breast cell lines propagated in vitro. Breastcancer tissue and the breast-cancer cell lines MCF-7, SK-BR-3 and ZR-75-1 showed expression of ICAM-1 and VLA-4 significantly lower than that of benign breast cells or nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…has also been demonstrated to induce ICAM-1 expression on several types of epithelial tumors including breast carcinomas. 29,30,39 In contrast, VCAM-1 has not been examined with respect to induction with TNF-␣; however, in other studies VCAM-1 has not been shown to be expressed by breast carcinoma cells. 14 RT-PCR, Western blotting, and cell surface ELISAs were used to examine adhesion molecule expression on several breast carcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…has also been demonstrated to induce ICAM-1 expression on several types of epithelial tumors including breast carcinomas. 29,30,39 In contrast, VCAM-1 has not been examined with respect to induction with TNF-␣; however, in other studies VCAM-1 has not been shown to be expressed by breast carcinoma cells. 14 RT-PCR, Western blotting, and cell surface ELISAs were used to examine adhesion molecule expression on several breast carcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] We first used RT-PCR to determine if these cells synthesized mRNA for various adhesion molecules. MDA-MB-435S and MDA-MB-468 cells both constitutively expressed high levels of mRNA for ICAM-1 ( Figure 1A).…”
Section: Expression Of Icam-1 and Vcam-1 Mrna By Breast Carcinoma Celmentioning
confidence: 99%
“…CD40 triggering of B-CLL cells could upregulate CD80, enhance the functional expression of signal 2 and increase the immunogenicity against allogeneic T cells ( Van den Hove et al, 1997;Buhmann et al, 1999). Furthermore, costimulation of CD80 amplified both CD4 and CD8 T-cell responses against tumour cells (Sule-Suso et al, 1995), and CD54 expression on tumour cells was important for tumour-cell killing, as well as being significant for an effective CD4 and CD8 T-cell activation (Budinsky et al, 1997;Croft et al, 1997). In a murine system, presentation of peptides by naive B cells or by CD54 2 /CD80 2 fibroblasts induced T-cell anergy, while activated B cells or CD54 1 / CD80 1 fibroblasts used as antigen-presenting cells induced T-cell activation (Croft et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…ICAM1 has been shown to play a role as a cell adhesion molecule and is related to immune responses. TNF-α has been found to reinduce expression of ICAM1, which was downregulated in breast cancer (Budinsky et al, 1997). Significantly downregulated cancerrelevant genes included POSTN (3.0-fold decrease in both 5 and 10 μM Aza treated cells) and NOTCH4 (3.0-fold decrease in 5 μM Aza treated cells and 5.0-fold decrease in 10 μM Aza treated cells).…”
Section: Aza Induced Genome-wide Demethylation In Mcf-7 Cellsmentioning
confidence: 99%